O ensino da história e da cultura afro-brasileira em Rondônia : a aplicação da lei nº 10.639/2003 - Silva, Simeia de Oliveira Vaz (2015)
The proposing investigation is agreed at study of the teaching of History and applicability of the Law 10.639/2003, above all Rondônia. The object of the research is History book handed out by PNLD 2012. The main objective is to find what is the vision from Africa History and Afro-Brazilian Culture presented in the didactic History books and if this vision permits the applicability of Law. This way, the research dis divided in three parts. Firstly, it seeks to understand the path that became possible application of Law 10.639/2003 through the analyses of documents as National Curricula Parameter (Parâmetros Curriculares Nacionais - PCNs) and orientações of Rondônia Education Secretariat (Secretaria de Educação de Rondônia - SEDUC). After analyses, it is discussed about indentity afro-rondoniense what it was built in intense migratory flow that it brings forth a identity crisis. Then it is made analyses of History books of the PNLD 2012 due to understand, if the Africa History and Afro-Brazilian Culture presented is capable to permit afro-rondoniense the recognition of their identity. Although, they presented a rich Africa, diverse and free from large stereotypes it is not possible to afro-rondoniense to recognize in it. Finally, the last part suggests a proposal to teach Afro-rondoniense History.